The digestive system (Chicago : Encyclopaedia Britannica Educational Corporation, 1981)
Explains the major chemical and mechanical processes by which the digestive system converts food to energy. The film clearly locates, identifies, and describes the function of each digestive organ, and stresses the importance of a well-balanced diet for providing the energy the body needs
Keywords: Digestion